This time tomorrow - Straub, Emma (Riverhead Books, 2022)
"What if you could take a vacation to your past, without the filter of memory? What would you give to go back in time and relive your youth, in person, with the people who shared it? On the eve of her 40th birthday, Alice's life isn't terrible. She likes her job, even if it isn't exactly the one she expected. She's happy with her apartment, her romantic status, her independence, and she adores her lifelong best friend. But something is missing. Her father, the single parent who raised her, is ailing and out of reach. How did they get here so fast? Did she take too much for granted along the way? When Alice wakes up the next morning somehow back in 1996, it isn't her 16-year-old body that is the biggest shock, or the possibility of romance with her adolescent crush, it's her dad: the vital, charming, 49-year-old version of her father with whom she is reunited. Now armed with a new perspective on her own life and his, is there anything that she should do differently this time around? What would she change, given the chance? With her celebrated humor, insight, and heart, Emma Straub cleverly turns all the traditional time travel tropes on their head and delivers a different kind of love story--about the lifelong, reverberating relationship between a parent and child"--